Migration Flows, Their Determinants and the Effects of Return Migration - Vanderkamp, John (Journal of Political Economy, 1971)
This paper examines at the theoretical level the distinction among new, return, and autonomous migration flows. This helps to explain the relative magnitudes of observed gross and net migration flows. Return migration has the effect of linking gross migration flows in opposite directions. The income-distance trade-off is strongly affected by the state of the labor market. Thus, not only is the overall level of migration reduced under depressed conditions, but the allocative efficiency of migration is also adversely affected.